Survei Ketersedian Sarana dan Prasarana PJOK di SD Generasi Unggul Bajawa - Ambros Niga; Fordianus Keo; Yanuarius Ricardus Natal (SMA Negeri 1 Bangkinang Kota, 2026)
ABSTRACT This study aims to identify the availability and condition of educational facilities and infrastructure at Generasi Unggul Bajawa Elementary School. A descriptive survey method was employed in this research. Data were collected through direct observation and the use of survey instruments covering school facilities, including classrooms, libraries, sanitation facilities, learning media, and other supporting infrastructure. The findings reveal that most facilities and infrastructure at Generasi Unggul Bajawa Elementary School are available and functional in supporting the learning process. However, several facilities are still not optimal in terms of quantity and condition and therefore require further improvement. Adequate facilities and infrastructure play a significant role in creating a comfortable learning environment and enhancing the quality of learning in elementary schools.